Fractional variable order discrete-time systems, their solutions and properties. Issue 14 (26th October 2017) - Sierociuk, Dominik; Malesza, Wiktor
ABSTRACT: In this paper, fractional variable order discrete state-space systems based on different definitions of fractional variable order difference are investigated.The general solution of these systems is derived. Moreover, necessary and sufficient conditions for reachability and observability are given and proven. The sufficient conditions for controllability are proposed too.